Fenomena Campur Kode dalam Deskripsi Produk Tokopedia: Kajian Sosiolinguistik - Novita Puspahaty; Siti Aulia Rachmah (Jurnal Bahasa dan Sastra, 2023)
Tokopedia, as one of the leading e-commerce platforms in Indonesia, presents a variety of products with interesting descriptions. This research analyzes the phenomenon of code-mixing in Tokopedia product descriptions, especially in the footwear and clothing categories. The purpose of this study is to identify the types of code mix used, and understand the underlying factors. This research uses descriptive qualitative method with purposive sampling technique. Data were collected from 25 product descriptions uploaded between August 22, 2022 and September 12, 2022. Data analysis refers to the theory of code-mixing from Musyken (2005) and the causal factors according to Hoffman (2017). The results show that there are three types of code-mixing, namely insertion, alteration, and congruent lexicalization. The underlying factors include topic need, lexical, group identity, and emphasis. This research contributes to the understanding of the use of code-mixing in the Indonesian e-commerce context, and opens up opportunities for further research related to its implications for consumer behavior and online marketing strategies.